Recruitment and Retention of Homeless Youth in a Substance Use and HIV-risk Reduction Program. Issue 1 (February 2018) - Garvey, Rick; Pedersen, Eric R.; D'Amico, Elizabeth J.; Ewing, Brett A.; Tucker, Joan S.
Conducting intervention studies with homeless populations can be difficult, particularly in terms of retaining participants across multiple sessions and locating them for subsequent follow-up assessments. Homeless youth are even more challenging to engage due to substance use, mental health problems, wariness of authority figures, and frequent relocations. This article describes methods used to successfully recruit a sample of 200 homeless youth from two drop-in centers in Los Angeles, engage them in a four-session substance use and sexual risk reduction program (79% of youth attended multiple sessions), and retain 91% of the full sample at a three-month follow-up assessment. Our experience indicates that utilizing structured project materials and having a small dedicated staff are essential to recruitment and retention efforts for intervention studies with homeless youth. Using these and other nontraditional methods are likely necessary to engage this at-risk yet hard-to-reach population.